Analisis Pola Pendidik Profesional Sesuai Karakteristik Islam - 'Aini, Lesmitul; Badriyah, Lailatul; Kastia Syahfitri, Nurul (Yayasan Darussalam Bengkulu, 2020)
Educator does not sound familiar among the people. An unsung hero is an educator. This writing aims for teachers to become professional educators in the teachings of Islam. There are indeed many teachers but not all teachers are professionals. Being a professional educator according to Islam is an educator who has a great sense of responsibility for the abilities of his students and provides scientific knowledge and religious knowledge.In addition to having knowledge and religion, professional educators must have good personalities, have good morals, have good character, have moral values, are virtuous and have good morals in accordance with Islamic teachings, because a teacher will be a role model for students and he also can be uplifting or provide motivation and inspiration to students and those around him with the abilities he had previously obtained.The professional teacher must have a goal, the goal of the professional teacher in Islamic teachings namely: to build a good society. social justice applies to every student, has a sense of tolerance, brotherhood, love, kindness and truth that stands out in students, individuals have freedom of thought in making decisions, able to live their lives happily. Therefore education is very important for a child, both general education and religious education.